1999
DOI: 10.1152/ajprenal.1999.276.1.f27
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of the electrogenic Na+- HCO 3 − cotransporter in mammalian and amphibian kidney

Abstract: Electrogenic cotransport of Na+ and[Formula: see text] is a crucial element of[Formula: see text] reabsorption in the renal proximal tubule (PT). An electrogenic Na+-[Formula: see text]cotransporter (NBC) has recently been cloned from salamander and rat kidney. In the present study, we generated polyclonal antibodies (pAbs) to NBC and used them to characterize NBC on the protein level by immunochemical methods. We generated pAbs in guinea pigs and rabbits by immunizing with a fusion protein containing the carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(158 citation statements)
references
References 30 publications
(54 reference statements)
12
144
1
1
Order By: Relevance
“…pNBC1 transcripts have also been detected in many organs, indicating the ubiquitous expression of this transporter (1). The second known NBC1 protein variant, kNBC1, is more restricted in its tissue expression and has thus far been detected in kidney and eye (8,29). Additional studies of the cellular/subcellular localization in various tissues, transport kinetics, and regulation of these electrogenic Na ϩ -HCO 3 Ϫ cotransporters are required to address the question as to why in the mammalian genome there are two distinct genes that encode electrogenic Na ϩ -HCO 3 Ϫ cotransporters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pNBC1 transcripts have also been detected in many organs, indicating the ubiquitous expression of this transporter (1). The second known NBC1 protein variant, kNBC1, is more restricted in its tissue expression and has thus far been detected in kidney and eye (8,29). Additional studies of the cellular/subcellular localization in various tissues, transport kinetics, and regulation of these electrogenic Na ϩ -HCO 3 Ϫ cotransporters are required to address the question as to why in the mammalian genome there are two distinct genes that encode electrogenic Na ϩ -HCO 3 Ϫ cotransporters.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, NBC1 encodes two electrogenic Na ϩ -HCO 3 Ϫ cotransport variants, kNBC1 and pNBC1, which differ in their NH 2 terminus (3). kNBC1 mediates the majority of basolateral HCO 3 Ϫ efflux in the renal proximal tubule (2,9,26,29). pNBC1 is highly expressed in pancreas and various other tissues (1,8,14,20,21).…”
mentioning
confidence: 99%
“…This result probably explains why we and others failed in our attempts to expression clone NBCe1 using mammalian mRNA. Bernhard Schmitt raised the first antibodies to the electrogenic NBC, and he and his colleagues demonstrated that the protein is expressed heavily at the basolateral membranes of the S1 and likely the early S2 segments of the renal PT (70).…”
Section: Cloningmentioning
confidence: 99%
“…It is therefore possible that mutations in the common NBC-1 region may affect the properties of all these isoforms, resulting in renal and extrarenal manifestations. For example, because kNBC-1 is thought to be responsible for a majority of HCO 3 -reabsorption from renal proximal tubules (10)(11)(12), its inactivation can readily explain the occurrence of pRTA. Recent studies (13,14) suggest that NBC-1 may also play a significant role in HCO 3 -transport by the corneal endothelium, which potentially could explain the occurrence of band keratopathy (4).…”
Section: Introductionmentioning
confidence: 99%